TGFβ signalling pathway regulates angiogenesis by endothelial cells, in an adipose‐derived stromal cell/endothelial cell co‐culture 3D gel model. (21st October 2015) - Lin, Shiyu; Xie, Jing; Gong, Tao; Shi, Sirong; Zhang, Tao; Fu, Na; Ye, Ling; Wang, Min; Lin, Yunfeng
Abstract: Objective: This study aimed to investigate the role of the TGFβ signalling pathway in angiogenesis in a three‐dimensional (3D) collagen gel model, with co‐culture between adipose‐derived stromal cells (ASCs) and endothelial cells (ECs). Materials and methods: A 3D collagen gel, implanted with green fluorescent protein‐labelled mouse ASCs and red fluorescent protein‐labelled mouse ECs, was established in vitro . Phenomena of angiogenesis with or without type I TGFβ receptor inhibitor (LY2157299) treatment, were observed 7 days post‐implantation, using confocal laser scanning microscopy. To detect expression of angiogenesis‐related genes, semi‐quantitative PCR and quantitative real‐time PCR were conducted. Zymography was performed to explore secretion of matrix metalloproteinase 2 (MMP‐2) and matrix metalloproteinase 9 (MMP‐9) after treatment with LY2157299 of 5, 10, 20 to 50 μm concentrations, for 24 h. Results: Angiogenesis was found to be attenuated in co‐culture gels after ASC and EC treatment with LY2157299. Genes VEGF‐A, VEGF‐B, VE‐ca, FGF‐1, FGF‐2, PDGF, HGF, BMP‐4 were significantly reduced in the presence of LY2157299 in both mono‐cultured and co‐cultured ECs. Furthermore, reduction in co‐cultured ECs was prominent relative to mono‐cultured ECs, while the same results did not occur to ASCs. We further confirmed that gelatinases secreted by ECs were reduced in a dose‐dependent manner, after treatment with LY2157299. Conclusions: These results indicate that in ASC/EC co‐culture, the TGFβ signalling pathway regulated angiogenesis via EC activity. Co‐cultured ECs were regulated more significantly than mono‐cultured ECs suggesting that inhibition of TGFβRI may regulate paracrine secretion of ASCs to further modulate EC angiogenesis.